STUDENT STRESS, COPING SKILLS, AND SCHOOL INTERVENTIONS: A LITERATURE REVIEW - Goff, Halee (Acta Scientiae et Intellectus, 2024)
Stress is an unavoidable entity in life. However, students are experiencing stress at heightened levels from a variety of sources. How students deal with the increased stress levels is of utmost importance for schools due to the direct correlation between a student’s ability to manage stress in a positive, productive manner and his or her academic success. The researcher conducted a review of the literature regarding the sources of stress for students, which coping strategies are employed by students, and the types of school-based interventions currently being used by schools as well as the effectiveness of the intervention programs. The results of the research indicated trauma, societal issues, and academic pressures are sources of stress for students while students are coping with the stress in positive manners, such as task and time management and diversions, as well as with negative mechanisms, such as unethical actions and substance abuse. Schools were found to be in a prime position to help students learn positive coping skills in the face of stressful situations; however, the need of mental health services and the amount of services being provided were found to be in contradiction of the other. The literature review found a need for continued research into preventative and intervention programs aimed at assisting students in stress management and mental health services.